Smart Marketing Transformation: Optimalisasi Promosi UMKM Melalui Ai, Chatgpt, Dan Sistem Informasi Manajemen - Teguh Setiadi; Edy Siswanto; Dendy Kurniawan; Ahmad Ashifuddin Aqham (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2025)
Micro, Small, and Medium Enterprises (MSMEs) contribute significantly to Indonesia’s economy; however, technological advancements and shifts in consumer behavior require MSMEs to adapt more rapidly to remain competitive. Digital transformation has become a strategic and inevitable step in facing the dynamics of the modern market. This study offers novelty through the integration of Generative AI (ChatGPT) with Management Information Systems (MIS) as an innovative model to enhance MSMEs’ digital marketing capabilities. Using a literature review method with a qualitative approach based on 2020–2025 publications from Google Scholar, this study identifies that the utilization of ChatGPT not only accelerates information processing and service automation but also supports real-time, data-driven marketing decision-making. The findings demonstrate that the ChatGPT–MIS collaboration can create a smart marketing ecosystem that strengthens MSMEs’ competitiveness by improving operational efficiency, personalizing customer services, and optimizing digital promotional strategies. Case studies on TikTok and Tokopedia Kenangan confirm that the adoption of AI-based digital technologies can expand market reach, increase sales conversion, and improve inventory management. Nevertheless, challenges such as uneven digital infrastructure and low technological literacy need to be addressed through continuous training and mentoring. This study asserts that integrating ChatGPT into MIS presents a relevant and innovative approach for MSMEs to adapt to an increasingly dynamic digital business ecosystem.